2020
DOI: 10.3390/en14010061
|View full text |Cite
|
Sign up to set email alerts
|

Dual and Ternary Biofuel Blends for Desalination Process: Emissions and Heat Recovered Assessment

Abstract: Desalination using fossil fuels is so far the most common technique for freshwater production worldwide. However, such a technique faces some challenges due to limited fossil fuels, high pollutants in our globe, and its high energy demand. In this study, solutions for such challenges were proposed and investigated. Renewable biofuel blends were introduced and examined as energy/sources for desalination plants and, in turn, reduced dependency on fossil fuels, enhanced pollutants, and recovered energy for desali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In many cases, full-open throttle engine tests were conducted, which was not the case in the current study. For instance, Elfasakhany [88] reported slightly higher CO and HC emissions for two steady states and the opposite trend for another steady-state test condition. In driving cycle test procedures, no definitive trends in HC or CO emissions were observed for increased alcohol content in the blends [89].…”
Section: Resultsmentioning
confidence: 95%
“…In many cases, full-open throttle engine tests were conducted, which was not the case in the current study. For instance, Elfasakhany [88] reported slightly higher CO and HC emissions for two steady states and the opposite trend for another steady-state test condition. In driving cycle test procedures, no definitive trends in HC or CO emissions were observed for increased alcohol content in the blends [89].…”
Section: Resultsmentioning
confidence: 95%
“…In addition, as a technology that will be an effective alternative desalination method in the future, the tidal system RO can save more money when the feed pressure or water extraction rate is high. To find solutions to challenges such as fossil fuel limitation, high pollution, and high energy demand on our globe, eight different renewable biofuel blends were presented and investigated by Elfasakhany [ 36 ] as energy sources for desalination plants. The results showed that both gasoline-bioethanol and gasoline-biomethanol provided high heat recovery and sensitive emissions of CO and UHC.…”
Section: Applications Of Renewable Energies In Agriculturementioning
confidence: 99%
“…The slight difference appears due to dissimilar combustion characteristics and flame propagations. Both the fuels are different in terms of heating values, saturation pressures, stoichiometric A/F ratios, boiling points and auto ignition temperatures, as summarized in Table 1 [149,150]. One further difference is the structure of both fuels, whereby i-butanol is branched-chain but n-butanol is a straight-chain.…”
Section: Comparison Between Single Biofuel Blends In Siementioning
confidence: 99%